Poverty Reduction and Growth Trust : 2020-21 Borrowing Agreements with The Government of Australia, Danmarks Nationalbank, The Bank Of Italy, The German Federal Ministry Of Finance On Behalf Of The Federal Republic Of Germany, And The Swiss National Bank. (Policy Papers; Policy Paper ;, 2021)
This paper presents to the Executive Board for information the second set of new borrowing agreements for the Poverty Reduction and Growth Trust.